PENERAPAN PSAK NOMOR 45 TENTANG PELAPORAN KEUANGAN ORGANISASI NIRLABA PADA SMK NEGERI 1 MANADO - Rantung, Mario; Sabijono, Harijanto; Tirayoh, Victorina Z. (Universitas Sam Ratulangi, 2019)
Along with the development of the world of education today, the Indonesian government is very serious in responding to the development of education to produce quality schools, this is also with considerable school activities. Things that must be accounted for and delivered through financial statements.This study aims to describe the presentation of financial reports on Nonprofit Organizations and to find out how to implement the application of PSAK number 45 concerning the Presentation of Financial Statements of SMK Negeri 1 Manado. The data research method used is qualitative analysis with qualitative analysis and quantitative analysis. Qualitative analysis to find out the comparative object of research is financial reporting at SMK Negeri 1 Manado with PSAK No. 45 and also with the preparation of budget and budget. Economic analysis to find out the values that arise from the financial statements of SMK Negeri 1 Manado The results of the analysis show that the preparation of financial statements at SMK Negeri 1 Manado has not been used to make financial statements, financial statements, and financial statements that are in accordance with the financial format contained in PSAK No. 45.